# Prove $(\cos^3\theta+\sin^3\theta)^2= \cos^6\theta(1+\tan^3\theta)^2$

## 2 answers

+2

−0

Simplifying $LHS$:

\begin{align} (\cos^3\theta+\sin^3\theta)^2&=\cos^6\theta+\sin^6\theta+2\cos^3\theta\sin^3\theta\\&=\cos^6\theta\bigg(1+\dfrac{\sin^6\theta}{\cos^6\theta}+2\dfrac{\cos^3\theta\sin^3\theta}{\cos^6\theta}\bigg)\\&=\cos^6\theta(1+\tan^6\theta+2\tan^3\theta)\\&=\cos^6\theta[1^2+(\tan^3\theta)^2+2(1)(\tan^3\theta)]\\&=\cos^6\theta(1+\tan^3\theta)^2\\&=RHS \end{align} Hence proved.

## 0 comment threads